Peluang dan tantangan usaha masker kain di masa Pandemi COVID-19 - Tety Suryany; Guspa Leviananda Rusta; Siti Rokmah Wulandari; Ahmad Muzakki; Yuli Herawati; Reysa Romadoni; Asih; Dias Rika Ashari; Maria Theresia Budiarti (Asosiasi Dosen Pemerhati Pendidikan Indonesia, 2022)
The purpose of this study was to analyze the opportunities and challenges of the fabric mask business during the COVID-19 pandemic. This research is a survey research with descriptive research. The source of the research data is the answers from respondents given to the fabric mask traders. The research data collection technique provided a questionnaire consisting of several questions asked about business opportunities and challenges during the COVID-19 pandemic. The questionnaire is a list of questions sent to respondents both directly and indirectly. Questionnaire can answer questions that can be answered in the form of a questionnaire. It can be concluded, that the business opportunity in the COVID-19 period is greater with a percentage of 50% of the results of the questionnaire, while threats of 50% of the results of the questionnaire. So, business opportunities and business challenges that will be faced as large. Keyword: Business opportunities, Business challenges, Fabric masks